The effective combination therapies with irinotecan for colorectal cancer - Chai, Yun; Liu, Jing-Li; Zhang, Shuo; Li, Na; Xu, Ding-Qiao; Liu, Wen-Juan; Fu, Rui-Jia; Tang, Yu-Ping (Frontiers in Pharmacology, 2024)
Colorectal cancer is the third most common type of cancer worldwide and has become one of the major human disease burdens. In clinical practice, the treatment of colorectal cancer has been closely related to the use of irinotecan. Irinotecan combines with many other anticancer drugs and has a broader range of drug combinations. Combination therapy is one of the most important means of improving anti-tumor efficacy and overcoming drug resistance. Reasonable combination therapy can lead to better patient treatment options, and inappropriate combination therapy will increase patient risk. For the colorectal therapeutic field, the significance of combination therapy is to improve the efficacy, reduce the adverse effects, and improve the ease of treatment. Therefore, we explored the clinical advantages of its combination therapy based on mechanism or metabolism and reviewed the rationale basis and its limitations in conducting exploratory clinical trials on irinotecan combination therapy, including the results of clinical trials on the combination potentiation of cytotoxic drugs, targeted agents, and herbal medicine. We hope that these can evoke more efforts to conduct irinotecan in the laboratory for further studies and evaluations, as well as the possibility of more indepth development in future clinical trials.